Pengaruh Electronic Word of Mouth (E-WOM) dan Promosi Media Sosial terhadap Minat Pembelian pada Produk Cataleyaonlineshop di Jakarta - Zahro, Fatimatu; Sholeh, Muhammad; Prehantio, Tri Waluyo; Amalia, Laila (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This study was motivated by the phenomenon of decreased interest in purchasing Cataleyaonlineshop products resulting in a decrease in revenue at Cataleyaonlineshop. The existence of possible causes of declining buying interest needs to be studied so that sales at Cataleyaonlineshop can increase again. This study is a study using quantitative research methods with descriptive research type. The data collection method used is a questionnaire. The population in this study is Cataleyaonlineshop customers with a total of 344 customers, sampling using the slovin formula as many as 77 samples. The results of the questionnaire were analyzed using test data instruments, namely validity test and reliability test, classical assumption test, correlation coefficient analysis and coefficient of determination, multiple linear regression analysis, t test and f test. The results of this study showed that the variable X1 produces positive results and significant to the purchase interest (Y) tthe count showed results of 16.836 > ttable of 0.677. The results of testing on variable X2 give positive and significant results on purchase interest (Y) tthe count shows results of 15.717 > ttable of 0.677. The results of the f test on the variable Electronic Word of Mouth (X1), social Media promotion (X2) together that significantly affect the Fhitung value of 193.831 > 3.12 Ftabel. And the value of the coefficient of determination of 0.840.